Rubens Corrêa é Artaud!: as manifestações (do) inconsciente/s no trabalho do ator [uma busca pela atuação esquizofrênica rubeniana] - Ríspolli, Guilherme Conrado Pereira (2018)
This essay seeks to bring out the discussion about the poetic power that is within the unconscious language of the actor’s work, by means of the schizophrenic process. To bring to light the work of Rubens Corrêa, brazilian actor and director, within the play Artaud! (1986), the reading suggest that the rubenian schizophrenic acting is part of the poetic madness present in the artaudian work-life. From the observation of the rehearsal-video made by Ipanema Theatre in partnership with the filmaker Gilberto Gouma, I search the inner dialogue within the theatrical-vital thoughts resulting from the Theatre of Cruelty and the studies about the unconscious manifestations in regard to acting. In this way, it is possible to recognize the qualities found in the schizophrenia for the acting process, since the vital scenic energy opens the paths to the human abyss, located within the unconscious region, the fragmentation of being and the lucidity of madness, that reveals the human being in their poetic essence/truth.